2011
DOI: 10.1186/1471-2180-11-248
|View full text |Cite
|
Sign up to set email alerts
|

The uncertain consequences of transferring bacterial strains between laboratories - rpoS instability as an example

Abstract: BackgroundMicrobiological studies frequently involve exchanges of strains between laboratories and/or stock centers. The integrity of exchanged strains is vital for archival reasons and to ensure reproducible experimental results. For at least 50 years, one of the most common means of shipping bacteria was by inoculating bacterial samples in agar stabs. Long-term cultures in stabs exhibit genetic instabilities and one common instability is in rpoS. The sigma factor RpoS accumulates in response to several stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 39 publications
(73 reference statements)
2
30
0
Order By: Relevance
“…Different environmental stresses are known to upregulate RpoS to varied levels (8), suggesting that some insensitive genes may only be expressed under certain stresses. In addition to the effects on gene expression, sensitivity to RpoS may also impact the effects of mutations in rpoS, which have been seen to evolve in the lab (52,53). We expect mutations attenuating RpoS have the strongest effect on insensitive genes and the weakest effect on sensitive genes.…”
Section: Discussionmentioning
confidence: 99%
“…Different environmental stresses are known to upregulate RpoS to varied levels (8), suggesting that some insensitive genes may only be expressed under certain stresses. In addition to the effects on gene expression, sensitivity to RpoS may also impact the effects of mutations in rpoS, which have been seen to evolve in the lab (52,53). We expect mutations attenuating RpoS have the strongest effect on insensitive genes and the weakest effect on sensitive genes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the strains had suffered few subcultures (about 5) and were stored at Ϫ80°C, they had been passaged twice in stabs for short periods. It has recently been reported that storage in stabs selects for partial or complete loss-of-function mutations in rpoS (59,60). The high level of rpoS mutations could be related to the storage conditions.…”
Section: Discussionmentioning
confidence: 99%
“…RpoS is an alternative sigma factor of RNA polymerase that regulates more than 10% of E. coli genes and plays a critical role in survival under conditions of exposure to several types of stress, including acid, heat, and oxidative stress (14,15). A particular case of in vitro evolution is the inactivation of crl (which modulates the balance between different sigma factors in the RNA polymerase holoenzyme, particularly RpoS [16][17][18]) or rpoS (19)(20)(21), during stab storage of E. coli or Salmonella strains or during nutrient starvation, which favors the inactivation of the general stress response. Regulatory networks are also dynamic in vivo.…”
mentioning
confidence: 99%